Tri Hita Karana Implementation Model in The Front Office Department at The Infinity8 Bali Hotel - Ni Kadek Jumiati Parwati; I Gede Mudana; Ni Made Sudarmini; Cokorda Istri Sri Widhari (Yayasan Sinergi Widya Nusantara, 2022)
Purpose: The purpose of this study was to know the implementation of Tri Hita Karana model applied in the Front Office Department at The Infinity8 Bali Hotel which is analyzed based on three variables of Tri Hita Karana, namely parhyangan, pawongan, and palemahan. Research methods: The data collection methods used were observation, questionnaires, Focus Group Discussion, and documentation. The data analy-sis method used is descriptive qualitative through data reduction, data presen-tation, and drawing conclusions. Findings: The implementation of Tri Hita Karana in the Front Office Depart-ment at The Infinity8 Bali Hotel is very suitable to be implemented as a whole with a total of 100% for Parhyangan, 93% for Pawongan, and 95% for Palemahan. Implication: The efforts that can be made to make the implementation of Tri Hi-ta Karana continues to be carried out consistently, namely Parhyangan by providing opportunities for employees to worship and apply religious values with mutual respect; Pawongan by giving rights and obligations to employees, the surrounding com-munity, and hotel guests; and Palemahan by building a harmonious relationship with the environmental sector, utilizing energy sources efficiently, and minimizing the use of materials that are harmful to the environment.